IMPLEMENTASI PRODUK INOVASI BERKELANJUTAN RAMAH LINGKUNGAN MELALUI EXPO PROJECT KEWIRAUSAHAAN MAHASISWA PROGRAM STUDI AKUNTANSI S1 UNIVERSITAS NEGERI MAKASSAR - Nurafni Oktaviyah; Suharti Sirajuddin; Yulia Yunita Yusuf; Anisatun Humayrah Rais; Fina Ruzika Zaimar (Universitas Ichsan Sidenreng Rappang, 2026)
The development of students’ entrepreneurial spirit has become one of the strategic efforts of higher education institutions in creating graduates who are creative, innovative, and adaptive to global challenges. One form of its implementation was carried out through the Entrepreneurship Expo Project 2026 organized by the Undergraduate Accounting Study Program, which adopted the theme of sustainable and environmentally friendly innovative products. This activity aimed to enhance students’ creativity, entrepreneurial skills, and awareness of the importance of environmental sustainability in product development. The activity was implemented using a project-based learning approach through product creation, booth exhibitions, product presentations, and evaluations conducted by judges and visitors. The participants consisted of students from seven classes who were divided into several business groups. Each group presented environmentally friendly innovative products with sustainability concepts and economic value. The event also featured Akmal Idrus, Founder and CEO of Rappo Indonesia, who delivered a sharing session on business opportunities and environmentally friendly business strategies for students. The results of the activity showed that students were able to create various creative products utilizing eco-friendly materials, recycled resources, and sustainable business concepts. In addition to improving entrepreneurial skills, the activity also strengthened students’ communication abilities, teamwork, and marketing strategies. The Entrepreneurship Expo Project became an effective applicative learning medium in supporting the development of entrepreneurial competencies among Undergraduate Accounting students in the field of sustainable entrepreneurship.